Les récits du spectateur. Mémoire et legende - Banu, Georges (2023)
This text aims to work out the issue of the production (written or oral) of narratives from a performance by the spectator as expressions of theatre imprint and of its impact in generating memories and legends. Those narratives show the deflagration of the lived instant experienced during the performance. They indicate at the same time the desire of perpetuating the feeling of absolute about what has just ended and to contribute to change the performance into a legend through the personal experience of the spectator. The presence and the unique irruption of the performer which concentrates fiction and reality in a same event activates the narration as well. To narrate is thus to start a trip with memory and imagination.